A Pilot Study Comparing Two Nonword Repetition Tasks for Use in a Formal Test Battery. (May 2015) - Tattersall, Patricia J.; Nelson, Nickola Wolf; Tyler, Ann A.
Two sets of nonwords (with and without true morphemes) were compared for their ability to differentiate students in Grades 1 through 12 with and without language impairment (36 each; N = 72) on a nonword repetition task. Results indicated that either nonword type could contribute to differential diagnosis.